Persuasion Through Semiotics: A Multimodal Analysis of Beverage Advertisements in Ghana - APPIAH, MICHAEL KWAME; Kyei, Emmanuel (International Journal of Language and Literary Studies, 2025)
This study explores the semiotic resources and embedded ideologies in billboard advertisements for beverages in Ghana, using a multimodal approach to understand how meaning is constructed and communicated. Although previous research in Ghana has primarily focused on linguistic elements, this study fills a gap by analysing a range of semiotic resources such as images, gestures, colours, symbols, typography, and text. Using Kress and Van Leeuwen's Visual Grammar Theory, the analysis of 20 advertisements from six Ghanaian beverage brands revealed key findings. The study found that semiotic resources like celebrity images, logos, and product visuals were strategically employed to establish brand identity and appeal. Gestures conveyed product advantages or participant emotions, while symbols (e.g., logos and world maps) reinforced brand image. Colour emerged as a powerful communicative mode, serving not only to capture attention but also to reinforce brand recognition and evoke culturally resonant meanings. Distinct brand colours—such as Coca-Cola's red and Guinness's black—were strategically used to strengthen identity and aid recall. Moreover, colours like yellow and green conveyed symbolic associations: yellow suggested energy and happiness, while green implied freshness and calm, aligning effectively with consumer aspirations and lifestyle preferences. These findings underscore how Ghanaian advertisers blend visual and textual elements to effectively persuade consumers, highlighting the role of cultural context in shaping advertising strategies.